ANALISIS KEMAMPUAN TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) CALON GURU SEKOLAH DASAR - Linda Zakiah; Wulandari, Nur; Hidayat, Elyana (Jurnal Pendidikan Dasar, 2021)
The ability of an educator in adjusting to the development of 21st-century learning must be met and becomes a challenge in itself. Therefore, students as prospective teachers must be able to meet these challenges. This effort is carried out so that students as prospective elementary school teachers can prepare superior human resources with global competencies and can adapt to the era of 21st-century learning. can be used to measure the mastery of Technological Pedagogical And Content Knowledge (TPACK) possessed by prospective elementary school teachers in elementary Civics learning courses by 21st-century learning. This study uses mixed methods. The method of approach used is explanatory sequential mixed methods. An explanatory sequential mixed methods research, the data collection procedure is divided into two stages, namely the preparation stage and the implementation stage.